2016
DOI: 10.1016/j.pmrj.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility and Effects of Acupuncture in an Adolescent Nordic Ski Population

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
15
0
4
Order By: Relevance
“…After removing duplicates (n = 31) from a total of 1990 records identified using the search strategy, 1959 studies were screened in view of the title, abstract, or full text, and 1937 were discarded (1558 studies were unrelated to sports medicine; 142 studies were not primary studies; 100 studies were experimental studies; 30 studies were not related to intervention using acupuncture points, etc.). Finally, 22 case reports/series were included in our review [27][28][29][30][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The summary of the characteristics of the inclusion studies based on the items in the CARE checklist is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplicates (n = 31) from a total of 1990 records identified using the search strategy, 1959 studies were screened in view of the title, abstract, or full text, and 1937 were discarded (1558 studies were unrelated to sports medicine; 142 studies were not primary studies; 100 studies were experimental studies; 30 studies were not related to intervention using acupuncture points, etc.). Finally, 22 case reports/series were included in our review [27][28][29][30][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The summary of the characteristics of the inclusion studies based on the items in the CARE checklist is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, sports injuries other than the musculoskeletal system were as follows. There were two studies [29,30] on exercise-related delayed onset muscle soreness (DOMS, 57 cases) and one study [40] on exercise-induced fatigue (41 cases) in athletes. Two studies reported mental and behavioral disorders such as yips for golfers (1 case) [37] and postconcussive symptoms (3 cases) [28].…”
Section: Demographic Information Main Concerns and Symptoms Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…No que se à prática terapêutica para redução de fadiga e recuperação muscular, a acupuntura (AC) tem sido amplamente utilizada para melhorar o treinamento da força, acelerar a recuperação dos treinos e danos, alcançar melhores condições fisiológicas e recuperar a fadiga muscular aguda (Lin et al, 2009;Garlanger et al, 2017) Jianjing). Usichenko et al (2009), apresentam estes pontos de AC como os de maiores valores no aumento de temperatura e consequente redução de fadiga no membro superior.…”
Section: Resultsunclassified
“…Compared to studies that failed to meet the inclusion criteria for this systematic review, inconsistent and heterogeneous findings appear to be the norm, with two studies 40,41 finding acupuncture to be more effective than a control, and one study finding that acupuncture did not significantly reduce post-exercise VAS among 20 male cyclists 42 . Furthermore, this review was able to include five studies and use a robust quality appraisal tool, which compares favourably to the two existing systematic reviews for DOMS 13,19 including two to four studies, neither of which have used the Cochrane quality assessment scale.…”
Section: Effectiveness Of Acupuncture For Doms Painmentioning
confidence: 95%